Strategic positioning of FELDA group towards achieving competitive advantage / Mohd Nazir Rabun - Rabun, Mohd Nazir (2014)
The concept of strategic positioning as a fundamental element in strategic management is used to understand how one important segment of public sector organisations, FELDA Group, a key player in the plantation industry, determines its strategic positioning towards achieving a competitive advantage. With the emergence of two dominant yet competing perspectives, the industrial organisation (10) view theory (Porter, 1980, 1985) and the resource-based view (RBV) theory (Wemerfelt, 1984; Barney, 1991) are used to examine the relationships. This research aims to examine determinants that form the bases of strategic positioning towards achieving a competitive advantage. This research examines the moderating variable that could affect the relationship between determinants of strategic positioning and achieving competitive advantage, namely the organisation’s age. A triangulation approach combining questionnaire and interviews was used in the study. There were 162 completed questionnaires returned, but only 150 were usable. To support the results from the quantitative data, semi-structured interviews were conducted with 2 Board Members of FELDA Group, who have broad and extensive perspective of the present situation of strategic management practices representing the influential group. The study found that the internal strategic capabilities factors in FELDA Group were highly influencing the achievement of competitive advantage. The focus of the FELDA Group managers has been to enhance the organisation’s performance and generate competitive advantage by strengthening its internal strategic capabilities factors in terms of human resources, financial position, leadership, organisational culture and organisational structure. Results also indicated that organisation's age was significantly moderated the relationship between stakeholders’ influencesexpectations factors and achieving competitive advantage.